2002
DOI: 10.1016/s1388-9842(02)00008-9
|View full text |Cite
|
Sign up to set email alerts
|

The addition of pentoxifylline to conventional therapy improves outcome in patients with peripartum cardiomyopathy

Abstract: We have reported previously that despite treatment with angiotensin-converting enzyme inhibitors and b blockers, the outcome of patients with peripartum cardiomyopathy (PPC) remains unfavorable. Similar to other etiologies of left ventricular dysfunction, we found elevated levels of tumor necrosis factor-a (TNF-a) in this group of patients. In the present study we sought to evaluate the effects of pentoxifylline, a drug known to inhibit the production of TNF-a, on clinical status, left ventricular function, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
1
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(98 citation statements)
references
References 15 publications
(18 reference statements)
1
86
1
10
Order By: Relevance
“…Baseline CRP, IL-6, TNF-a, and higher NYHA FC were the only predictors of mortality. These results contribute to inflammation which may contribute to the pathogenesis of PPCM and its complications [7,8,22]. Graph 2 Baseline plasma inflammatory markers of deceased patients versus survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline CRP, IL-6, TNF-a, and higher NYHA FC were the only predictors of mortality. These results contribute to inflammation which may contribute to the pathogenesis of PPCM and its complications [7,8,22]. Graph 2 Baseline plasma inflammatory markers of deceased patients versus survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Elevations of troponin T (TnT) appear to have prognostic significance in this group. The TnT level C0.04 ng/ml at presentation predicts persistence of systolic dysfunction with a sensitivity of 55 % and specificity of 91 % [8]. Inflammatory cytokines (TNF-a and IL-6) are elevated in women with PPCM compared to pregnancy controls [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This includes pentoxifylline, a drug reducing the production of TNF-alpha and preventing apoptosis, which despite the positive results of one study has not spread more widely 24 . The previously mentioned drug bromocriptine, a prolactin inhibitor used for years to suppress lactation, is currently often discussed.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, this agent has not shown any benefit in randomised controlled trials in terms of resolution of symptoms and improvements in ventricular function. 32 A more recent, non-randomised prospective study has suggested a potential benefit for anti-tumour necrosis factor α therapy with pentoxyfylline 33 although trends have not yet been corroborated in more established studies.…”
Section: Current Researchmentioning
confidence: 99%